Histopathological changes in the gill, liver and intestine of Heteropneustes fossilis (Bloch) treated with three dry seed extracts - Nasiruddin, Munira; Azadi, Mohammad Ali; Jahan, Aklima (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Acute toxicity tests were carried out with aqueous and ethanolic extracts of three botanicals Lagerstroemia speciosa (L.) Pers, Dipterocarpus turbinatus Gaertn and Hevea brasiliensis (Willd. Ex Juss) on Heteropneustes fossilis (Bloch) under normal laboratory conditions. Extracts of L. speciosa were more potent than the extracts of D. turbinatus and H. brasiliensis. Histopathological changes in gill, liver and intestine of exposed fishes caused subtle cellular damages like disintegration of gill filaments and lamellae, degeneration of hepatocytes and blood vessels and necrosis of the intestinal epithelia. Different seed extracts showed histopathological variations in the different organs depending on the toxicity of the plant extracts. On the basis of histopathology, effectivity of the extract was in the order: Absolute ethyl alcohol > 50% ethyl alcohol > distilled water and the effectivity of the seed extracts on the studied organs was: L. speciosa > D. turbinatus > H. brasiliensis seed extracts. DOI: http://dx.doi.org/10.3329/jasbs.v38i2.15612 J. Asiat. Soc. Bangladesh, Sci. 38(2): 217-226, December 2012